2021
DOI: 10.1016/j.gie.2020.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy for patients with achalasia with previous Heller myotomy: a systematic review and meta-analysis

Abstract: Background and Aims: Heller myotomy (HM) is considered the standard surgical treatment for patients with achalasia. However, approximately 10% to 20% of patients with achalasia have persistent or recurrent symptoms after HM that require further therapy. Several studies have reported the outcomes of peroral endoscopic myotomy (POEM) in these patients. We performed a systematic review and meta-analysis to evaluate the efficacy and safety of POEM in patients with achalasia with previous HM.Methods: An electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, when POEM is chosen to treat recurrent disease, greater technical success rates, 94 to 99.3%, have been reported. 16,17 Reported clinical success rates of POEM after previous LHM or endoscopy range from 76 to 96.8%. [16][17][18] Mean reduction in Eckardt score was 5.77 with a mean reduction in LES pressure of 18.3 mmHg.…”
Section: Reinterventionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when POEM is chosen to treat recurrent disease, greater technical success rates, 94 to 99.3%, have been reported. 16,17 Reported clinical success rates of POEM after previous LHM or endoscopy range from 76 to 96.8%. [16][17][18] Mean reduction in Eckardt score was 5.77 with a mean reduction in LES pressure of 18.3 mmHg.…”
Section: Reinterventionmentioning
confidence: 99%
“…16,17 Reported clinical success rates of POEM after previous LHM or endoscopy range from 76 to 96.8%. [16][17][18] Mean reduction in Eckardt score was 5.77 with a mean reduction in LES pressure of 18.3 mmHg. 18 Very few studies have compared reoperative Heller esophagomyotomy to other treatment modalities.…”
Section: Reinterventionmentioning
confidence: 99%
“…[48][49][50] In a recent systematic review (9 studies, 272 patients), the pooled clinical success after POEM was 90% (95% CI 83.1-96.8%). 51 Considering its excellent safety and efficacy, recent guidelines published by prominent gastrointestinal (GI) societies have included POEM in the management protocol for achalasia. [52][53][54][55] The management in cases with relapse of symptoms after POEM has not been studied well.…”
Section: Discussionmentioning
confidence: 99%
“…POEM has also been used to treat patients after LHM has failed. A recent meta-analysis on 9 retrospective studies from specialized high-volume centers reported satisfactory results in 90% of 270 patients treated, with adverse events in only 10.8% of cases (most of them minor, involving conservatively managed mucosal perforations) [ 23 ]. POEM is particularly attractive in this context because it enables an extended myotomy in a new plane (different from the anterior one) to be completed more easily and with fewer risks than a laparoscopic revision.…”
Section: Per-oral Endoscopic Myotomy (Poem)mentioning
confidence: 99%